Imaging acoustic sources through scattering media by using a correlation full-matrix filter. Issue 1 (December 2018) - Rui, Wei; Tao, Chao; Liu, Xiaojun
Abstract In the inhomogeneous medium, acoustic scattering is always a fundamental challenge for photoacoustic imaging. We implement a correlation full-matrix filter (CFMF) combing with a time reversal operator to improve the imaging quality of acoustic sources in complex media. The correlation full-matrix filtering process extracts the direct wave component from the detected signal and preserve all the useful information at the same time. A location factor is considered in the time reversal operator to compensate for the image distortion and false contrast caused by the limited-view detection. The numerical simulations demonstrate that the proposed approach can perform good imaging quality with the higher image signal-noise ratio and better resolution in an acoustic scattering environment. This scheme might be applied to improve the photoacoustic imaging for inhomogeneous biological tissues.